Evolution of Physicochemical Properties, Phenolic Acid Accumulation, and Dough-Making Quality of Whole Wheat Flour During Germination Under UV-B Radiation - Tian, Chao; Wang, Yue; Yang, Tianbao; Sun, Qingjie; Ma, Meng; Li, Man (Frontiers in Nutrition, 2022)
The effects of UV-B radiation on the physiological properties, phenolic acid accumulation and dough making quality of wheat during germination were investigated. UV-B radiation inhibited the wheat sprout length and reduced the dry matter loss. As phenolic acids were principally present in the kernels’ bran, UV-B radiation could promote the accumulation of them in the interior of germinated wheat. The total phenolic compounds, ascorbic acid, and antioxidant activity were also enhanced significantly during germination with UV-B. UV-B improved the development time, stability time, rheological properties and viscosity of germinated wheat, inhibited the α-amylase activity, the destruction of the amorphous region of starch particles, and the proteins degradation process during germination, thus the deterioration of dough making quality caused by germination was inhibited. Therefore, UV-B radiation could be a potential approach to enhance the nutritional and dough making quality of germinated whole wheat flour.